More talk than action: gender and ethnic diversity in leading public health universities. Issue 10171 (9th February 2019) - Khan, Mishal Sameer; Lakha, Fatim; Tan, Melisa Mei Jin; Singh, Shweta Rajkumar; Quek, Rina Yu Chin; Han, Emeline; Tan, See Mieng; Haldane, Victoria; Gea-Sánchez, Montserrat; Legido-Quigley, Helena
Summary: Improving the career progression of women and ethnic minorities in public health universities has been a longstanding challenge, which we believe might be addressed by including staff diversity data in university rankings. We present findings from a mixed methods investigation of gender-related and ethnicity-related differences in career progression at the 15 highest ranked social sciences and public health universities in the world, including an analysis of the intersection between sex and ethnicity. Our study revealed that clear gender and ethnic disparities remain at the most senior academic positions, despite numerous diversity policies and action plans reported. In all universities, representation of women declined between middle and senior academic levels, despite women outnumbering men at the junior level. Ethnic-minority women might have a magnified disadvantage because ethnic-minority academics constitute a small proportion of junior-level positions and the proportion of ethnic-minority women declines along the seniority pathway.